Effects of Low Moisture Extrusion on the Structural and Physicochemical Properties of Adlay (Coix lacryma-jobi L.) Starch-Based Polymers. (September 2020) - Zhang, Gaopeng; Ni, Chunlei; Ding, Yangyue; Zhou, Hualu; Caizhi, Ou; Wang, Qiuye; Wang, Jiarong; Cheng, Jianjun
Graphical abstract: Highlights: Starch conversion is not fully achieved by low moisture extrusion. Protein and lipids weaken the caramelization reaction of starch during extrusion. Lipids increase the pits in the extruded starch, and protein reduces the lacunas. Protein and lipids reduce the degree and temperature range of starch gelatinization. Abstract: This study investigated the changes in the structural and functional properties of various adlay starch-based polymers that occur during low moisture extrusion. The water absorption index, water solubility index, color, and morphological, pasting, and thermal properties of the adlay flours were investigated. Extrusion significantly decreased their contents (starch > protein > fiber > lipids). The color of the adlay flour darkened after extrusion, primarily due to the Maillard reaction and caramelization. Scanning electron microscopy revealed various cracks, pits, and holes on the surface of the extruded flour without defatting for both the extruded brown adlay and the extruded polished adlay. Extrusion caused molecular degradation of the extruded starch, decreasing its swelling power in hot water. The Δ H values (0.19-0.71 J/g) of the extrudates revealed that the starch granules were not fully gelatinized. These results provide a theoretical basis for further explorations of the interactions of adlay macromolecules by extrusion.